2022
DOI: 10.1002/hep4.1932
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of physical activity, muscular fitness, adiposity, and genetic risk for NAFLD

Abstract: Genetic predisposition and unhealthy lifestyle are risk factors for nonalcoholic fatty liver disease (NAFLD). We investigated whether the genetic risk of NAFLD is modified by physical activity, muscular fitness, and/or adiposity.In up to 242,524 UK Biobank participants without excessive alcohol intake or known liver disease, we examined cross-sectional interactions and joint associations of physical activity, muscular fitness, body mass index (BMI), and a genetic risk score (GRS) with alanine aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…One cross-sectional study examined interactions and joint associations of physical activity and a genetic risk score with NAFLD defined by alanine aminotransferase (ALT) levels. 29 Indeed, physical activity and sedentary behaviour can modulate the effect of the PNPLA3 variant on childhood NAFLD. 30 Compared with previous studies, the prospective design of the present study is more able to prove a cause-effect relationship and incorporates a much more comprehensive indicator of genetic risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One cross-sectional study examined interactions and joint associations of physical activity and a genetic risk score with NAFLD defined by alanine aminotransferase (ALT) levels. 29 Indeed, physical activity and sedentary behaviour can modulate the effect of the PNPLA3 variant on childhood NAFLD. 30 Compared with previous studies, the prospective design of the present study is more able to prove a cause-effect relationship and incorporates a much more comprehensive indicator of genetic risk.…”
Section: Discussionmentioning
confidence: 99%
“…One cross‐sectional study examined interactions and joint associations of physical activity and a genetic risk score with NAFLD defined by alanine aminotransferase (ALT) levels 29 . Indeed, physical activity and sedentary behaviour can modulate the effect of the PNPLA3 variant on childhood NAFLD 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity and NAFLD are intricately linked. There is a robust and consistent body of epidemiological evidence demonstrating regular PA reduces the risk of NAFLD, especially if guideline-based amounts of activity are achieved (7)(8)(9)(10)(11)(12)(13)21). Over time, consistently performing regular moderate-to-vigorous PA (MVPA) can lead to lower mortality overall and from CVD (8), even if performed in short, continuous bouts of at least 10 min in length (21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, NASH-cirrhosis continues to grow as a leading reason for liver transplantation (5,6). Although regular physical activity (PA) has many wellestablished benefits and may prevent or delay NAFLD and its complications, most individuals with NAFLD are inactive and fail to achieve recommended amounts of PA (7)(8)(9)(10)(11)(12)(13)(14)(15). In this roundtable document, the benefits of PA are discussed, along with recommendations for 1) PA assessment and screening; 2) how best to advise, counsel, and prescribe regular PA; and 3) when to refer a patient with NAFLD to an exercise specialist.…”
mentioning
confidence: 99%
“…5 However, physical activity as a tool to offset increased genetic risk for NAFLD remains relatively unexplored. A recent study by Schnurr et al 6 examined the effect of physical activity on the genetic risk conferred by a polygenic risk score using 68 loci for elevation in alanine aminotransferase (ALT) as a surrogate for NAFLD in 250 000 participants from the UK. The authors observed that increased physical activity modestly attenuated genetic predisposition to elevated ALT level.…”
Section: Sweating It Out: How Physical Activity Can Combat High Genet...mentioning
confidence: 99%